Третья террористическая: роман / А. А. Ильин - Ильин Андрей Александрович (ЭКСМО, 2003)
Экземпляры: ф.7 (20080619) / Инвентарный номер: 42057 / Цена: 60.00 / Авт.знак: И 46 / ГРНТИ: 17.82 / ББК: 84(2Роc=Рус)6